2017
DOI: 10.1063/1.4974040
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic theory of turbulent acceleration of parallel flow and momentum conservation

Abstract: Intrinsic flow in plasma physics is a long-standing puzzle, since it is difficult to understand its origin without contradiction to momentum conservation in conventional wisdom. It is proved that the electromagnetic turbulent acceleration as a candidate for intrinsic parallel flow generation driven by pressure gradient along the total magnetic field line does not contradict momentum conservation. The conserved quantity corresponding to axial symmetry is the total gyrocenter parallel canonical momentum carried … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Then, we extended our theory to electromagnetic ITG turbulence and found the importance of electromagnetic effects on intrinsic parallel rotation drive [15]. Finally, we demonstrated that the conserved quantity corresponding to axisymmetry is the total canonical momentum or total momentum carried by both particles and electromagnetic fields, and the presence of turbulent acceleration does not imply its confliction with momentum conservation [16].…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Then, we extended our theory to electromagnetic ITG turbulence and found the importance of electromagnetic effects on intrinsic parallel rotation drive [15]. Finally, we demonstrated that the conserved quantity corresponding to axisymmetry is the total canonical momentum or total momentum carried by both particles and electromagnetic fields, and the presence of turbulent acceleration does not imply its confliction with momentum conservation [16].…”
Section: Introductionmentioning
confidence: 76%
“…Through equations (14) and 15, we can obtain the same mean field equation of the parallel flow velocity (i.e., equation 11) regardless of the sequence of taking flux average and decoupling the parallel flow from parallel momentum density [16]. Therefore, the presence of the turbulent acceleration does not result from regrouping terms as one may wonder.…”
Section: Turbulent Acceleration and Momentum Conservationmentioning
confidence: 98%
See 3 more Smart Citations